Potensi Lokal dan Gerakan Sosial Baru: Kasus Kesiapan Masyarakat Menghadapi Pandemi COVID-19 Gelombang II di Perdesaan Madura - Hoiril Sabariman; Dessy Hidayati Fajrin; Qurnia Indah Permata Sari (Sociology Department, Brawijaya University, 2022)
Covid-19 pandemic has had a multidimensional impact, especially on the health and socio-economic of the community. However, the people of Ponteh Village are not too affected by the socio-economic impact. New social movements during the pandemic resulted in community readiness in the face of the second wave of the Covid-19 pandemic. Through qualitative approaches and case study methods, this article explains the various efforts made by citizens and new social movements during the Covid-19 pandemic. Data collection through participation observations, interviews, airy notes, and documentation studies. The results of this study show that the people of Madura have a social system in the form of family ties and social closeness to deal with difficult conditions. Community efforts in dealing with the pandemic, first, maximize local potential in the form of a collective economic orientation. Second, the people of Ponteh Village do the storage of agricultural commodities and control their sales of agricultural products. The study also showed three new social movements during the Covid-19 pandemic. First, the social movement of citizens who have social solidarity is expressed in the attitude of helping each other, please-help, cooperation, and caring for each other. Second, community leaders, namely kiai, have an important role in dealing with difficult conditions due to the impact of the pandemic, especially education about understanding health protocols. Third, the village government made several efforts beyond the assistance of the central government to deal with the impact of the Covid-19 pandemic. New social movements grew during the Covid-19 pandemic, resulting in a public readiness to deal with the second wave of pandemics.